Reassessing the Reserve Component: A Critical Review of Indonesia’s Law on the Management of National Resources for State Defense - Al Araf (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This paper examines the legal and conceptual issues surrounding Law No. 23/2019 on the Management of National Resources for National Defense (PSDN), with a particular focus on the management of the Reserve Component. It argues that the PSDN Law contradicts several constitutional principlesand established legal norms in Indonesia. The analysis highlights four key areas of concern:(1) the excessively broad role assigned to the Reserve Component in addressing hybridthreats, which risks blurring the boundaries between military and civilian functions; (2) Article 75’s provision allowing the use of regional government budgets to fund reserve components, which undermines the constitutional principle of centralized military financing; (3) the divergence of Indonesia’s Reserve Component policy from international trends that increasingly emphasize defensediplomacy, professionalism of security actors, and voluntary service; and (4) the problematic expansion of the Reserve Component’s role within the national security architecture. The paper concludes that a reorientation of defense priorities is necessary, to the one that focuses on the modernization of Indonesia’s primary weapons systems and the welfare of its professional military personnel, while ensuring that the Reserve Component operates within a